MALT lymphoma in terminal ileum a case report - Indrawati, Yeti (Jurnal Biomedik : JBM, 2016)
Abstrak: Mucosa associated lymphoid tissue lymphoma (MALToma) merupakan subtipe ketiga tersering dari limfoma non-Hodgkin. Gejala klinis sering insidius sebagai lesi yang low grade dan cenderung terlokalisasi untuk waktu lama. Saluran cerna, terutama lambung, merupakan lokasi ekstranodal tersering. MALToma dari ileum jarang ditemukan dengan patogenesis yang tidak diketahui pasti. Mengenai 5-year survival untuk MALToma dilaporkan 81%. Kami melaporkan kasus seorang laki-laki berusia 80 tahun dirawat di Bagian Emergensi RS Siloam Manado dengan nyeri abdomen dan adanya massa dalam abdomen. Pemeriksaan radiologi abdomen dan USG memperlihatkan adanya massa pada area usus halus. Pada pasien ini dilakukan laparotomi. Hasil histopatologik menunjukkan suatu MALT limfoma dari ileum terminalis.Kata kunci: MALT limfoma, ileum terminalis.Abstract: Mucosa associated lymphoid tissue lymphoma (MALToma) is the third most common non-Hodgkin’s lymphoma subtype. Clinical presentation is often insidious as a low grade lesion and the disease tends to remain localized for a long period of time. The gastrointestinal tract, but in particular the stomach, is by far the most common extra-nodal site. MALToma of ileum, however is rare. Little is known with certainty about the pathogenesis of the disease but overall 5-year survival for MALToma is reported as 81%. We reported an 80-year-old male presented to the Emergency Department of Siloam Hospital Manado with abdominal pain and an abdominal mass. He underwent an abdominal radiology and abdominal ultrasound which showed a mass in the small intestinal area. A laparotomy and a tumor biopsy were performed on him. The histopathological result was consistent with MALT lymphoma of terminal ileum.Keywords: MALT lymphoma, terminal ileum